Book review. Silent Voices: The Mental Health of Adolescents in the Decade of Change. - Fernández , Aida (Revista de Estudios Socioeducativos. ReSed, 2024)
Review of the book Silent Voices: The Mental Health of Adolescents in the Decade of Change, by Telmo Lazkano, Social Network Educator and Maitane Ormazabal, Therapeutic Coach. The book gives an analysis of the reality of adolescents' emotional growth in today's world, delving into the different elements of change in our society, highlighting the role our social environment plays in our individual development and exposing the causes for the many psychological disorders that affect teenagers. All of this is done in a very accessible style.